Pengaruh Kepercayaan, Persepsi Harga dan Sikap Terhadap Niat Beli Konsumen pada Grocery Banda Aceh - Nara Pristiwa; Aida Fitri (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
The purpose of this study is to ascertain how trust, price perception, and attitude affect consumers of Grocery Banda Aceh's purchase intentions. The quantitative method employed in this study tries to ascertain the influence or link between two or more study variables. There were 96 respondents in the study's samples. Non-probability sampling is used for data collecting, and accidental sampling is the method used. A questionnaire, a list of questions, and an examination of the supporting documents were used to gather research data. At the 95% confidence level (α = 0.05), hypothesis testing utilizing multiple linear regression analysis, F test (simultaneously), and t test (partial) is meant to ascertain the impact of the independent variable on the dependent variable. According to the study's findings, consumers' purchase intentions at Grocery Banda Aceh are influenced by attitudes, perceptions of price, and trust at the same time. Then, at Grocery Banda Aceh, Belief, Price Perception, and Attitude have some influence on consumer Purchase Intention. In light of this research's conclusions, consumers repurchase intentions at Grocery Banda Aceh may be increased by trust, pricing perception, and consumer attitudes